Perspectives on Finances and Mental Health Status among Low-Income Los Angeles Latinas - Luisa R Blanco; Jessica A Baker; Julie A Friedman; Karen T Singh; Arleen F Brown; Sierra D. Moon; Savanna L. Carson; Audree Hsu; Janet Pregler (Journal of Financial Therapy, 2020)
Abstract Research has established a link between financial challenges and mental health outcomes. Understanding this linkage among low-income Latinas who face unique experiences and challenges in relation to managing their household finances is important. This study utilized a community-based participatory qualitative research method to explore perspectives on financial and mental health among Latinas residing in Los Angeles County. The implications of this study are applicable when conducting a culturally responsive financial therapy program. Three focus groups were conducted with mainly immigrant, Spanish-speaking, low-income Latinas (n = 37). The study found that though participants face financial stressors tied to managing finances, they were eager to learn new skills and tools for improved financial practices and mental health therapies. For financial education interventions targeted to Latinas, it is best to use interventions that incorporate peer-support groups, improve knowledge about financial management tools and financial products available in the community, and therapeutic interventions to address financial stress. Key words: immigrants, household financial decision-making, savings, formal financial services, financial stress
Keywords: Undocumented; Documented; Latina; Low-Income Women; Mental Health; Finances